Risk of Progressive Multifocal Leukoencephalopathy in the Combination Antiretroviral Therapy Era in the French Hospital Database on Human Immunodeficiency Virus (ANRS-C4). (4th April 2018) - Melliez, Hugues; Mary-Krause, Murielle; Bocket, Laurence; Guiguet, Marguerite; Abgrall, Sophie; De Truchis, Pierre; Katlama, Christine; Martin-Blondel, Guillaume; Henn, Aurelia; Revest, Matthieu; Robineau, Olivier; Khuong-Josses, Marie-Aude; et al.
Abstract : We studied risk factors for progressive multifocal leukoencephalopathy in human immunodeficiency virus-infected individuals. Recent combination antiretroviral therapy initiation was associated with a transient increase in the risk of progressive multifocal leukoencephalopathy. Injection drug users and hepatitis C virus-seropositive individuals were at a higher risk, while sub-Saharan African origin was not protective. Abstract: Background: Risk factors for progressive multifocal leukoencephalopathy (PML) in individuals with human immunodeficiency virus (HIV) infection are poorly documented in the era of combination antiretroviral therapy (cART). Methods: We studied HIV-1–infected individuals aged ≥15 years who had no history of PML and were prospectively followed up between 1997 and 2011 in the French Hospital Database on HIV (FHDH-ANRS CO4) cohort. Cox models were used to calculate adjusted hazard ratios (HRs), focusing on sub-Saharan origin, suggested to be protective, and recent cART initiation, potentially associated with an increased risk of PML. Results: PML developed in 555 individuals, in 57 during the first 6 months of cART. From 1997–2000 to 2009–2011, the incidence fell from 1.15 (95% confidence interval [CI], .98–1.31) to 0.49 (.37–.61) per 1000 person-years. Sub-Saharan African origin had no clear influence (HR, 0.80; 95% CI, .58–1.11). Compared with men who have sex with men, injection drug users (IDUs) were at higher risk (HR, 1.80 [95% CI, 1.32–2.45] for male and 1.68 [1.13–2.48] for female IDUs). When IDUs were excluded, hepatitis C virus seropositivity was associated with an increased risk (HR, 1.40; 95% CI, 1.02–1.93). Compared with no cART initiation, initiation <6 months previously was associated with PML onset (HR, 4.91; 95% CI, 2.42–9.95). Conclusions: Recent cART initiation is associated with an increased risk of PML, as are injection drug use and hepatitis C virus seropositivity. Sub-Saharan African origin had no protective effect.